Subversive Creativity in an Aspirational Organization: How Burning Man Actualizes Behaving in a Loving Way (Journal of Organizational Psychology, 2020)
The Burning Man Project organization and the execution of the Burning Man event are presented as exemplars illustrating the actualization of behaving in a loving way. Burning Man is characterized as an aspirational organization that has created a set of 10 Burning Man Principles that reflect the values of the community of Burning Man as well serving as a guide to organizational decision-making. The 10 Principles are examined from the perspective of behaving in a loving way. The paper concludes with theoretical framework illustrations and qualitative data examples from Burning Man participants and events.
Keywords: Organizational Psychology; aspirational organization; subversive creativity; burning man